Calcined eggshells in anaerobic digestion: Buffering acidification in AD and evaluating end products from phosphate adsorption as soil conditioners - Photiou, Panagiota; Vyrides, Ioannis (My University, 2022)
The conversion of biowaste to a material that can improve environmental processes contributes to the circular economy. This study uses calcined eggshells as a new approach to counteract excessive acidification and alleviate low pH in anaerobic digestion. Calcined eggshells (900 °C, 30 min) addition in AD systems fed with 8 g L-1 glucose alleviated pH drop and showed substantially higher methane generation than the control. The pH value at the control was 5.63 due to the high VFAs, which severely inhibited the AD process, while after the addition of calcined eggshells, the pH was 7.13 producing significantly higher methane. Soluble CO2 had a higher adsorption affinity towards calcined eggshells than phosphates and negatively influenced the phosphate adsorption; however, this contributes to pH increase. By contrast, flushing with N2 showed high phosphate removal. Furthermore, calcined eggshells demonstrated high phosphate removal for anaerobic dewatered sludge leachates and anaerobic effluent wastewater (>78.4%) within the first 20 min. After the adsorption/precipitation of phosphate from anaerobic effluent, the solid residue positively affected plant growth for Sinapis alba and Lepidium sativum seeds. This new proof of concept contributes to the circular economy; the calcined eggshells are integrated with anaerobic digestion both in-situ for buffering acidification and ex-situ for phosphate removal and potential use as a soil conditioner.
Keywords: Anaerobic digestion; Buffer acidification; Calcined eggshells; Circular economy; Phosphate recovery